2022
DOI: 10.1101/2022.11.06.513053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complex third-party effects in theDictyostelium-Paraburkholderiasymbiosis: prey bacteria that are eaten, carried, or left behind

Abstract: Symbiotic interactions change depending on the abundance of third parties like predators, prey, or pathogens. Third-party interactions with food bacteria are central to the symbiosis betweenDictyostelium discoideumsocial amoeba hosts and inedibleParaburkholderiabacterial symbionts. Symbiosis withParaburkholderiaallows hostD. discoideumto carry food bacteria through the dispersal stage where host amoebae aggregate and develop into fruiting bodies that disperse spores. Carrying bacteria benefits hosts when food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Paraburkholderia infection is known to cause numerous phenotypes in D. discoideum hosts, including conferring the ability to carry food bacteria (DiSalvo et al 2015;Brock, Jones, et al 2016) and a reduction in predation ability (Scott, Queller, and Strassmann 2022b). A prior study showed that D. discoideum clones naturally infected by Paraburkholderia had fewer sentinel cells than naturally uninfected D. discoideum clones (Brock, Callison, et al 2016).…”
Section: Are Symbiont Paraburkholderia the Causal Agents For Immune-l...mentioning
confidence: 99%
See 1 more Smart Citation
“…Paraburkholderia infection is known to cause numerous phenotypes in D. discoideum hosts, including conferring the ability to carry food bacteria (DiSalvo et al 2015;Brock, Jones, et al 2016) and a reduction in predation ability (Scott, Queller, and Strassmann 2022b). A prior study showed that D. discoideum clones naturally infected by Paraburkholderia had fewer sentinel cells than naturally uninfected D. discoideum clones (Brock, Callison, et al 2016).…”
Section: Are Symbiont Paraburkholderia the Causal Agents For Immune-l...mentioning
confidence: 99%
“…The interaction between D. discoideum and these Paraburkholderia species has both positive and negative consequences for both participants, and is a rising model system in the study of the evolution of interspecific interactions (Scott, Queller, and Strassmann 2022a;Garcia et al 2019;Brock et al 2011;Brock et al 2013;DiSalvo et al 2015). A heretofore largely unexplored direction, however, is how infection by Paraburkholderia may modulate D. discoideum's interactions with other bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Carriage allows host amoebae to seed out populations of prey bacteria that hosts can then eat ( Brock et al, 2011 ). However, the ability to carry comes at the cost of reduced spore production when edible bacteria are common ( DiSalvo et al, 2015 ; Scott, Queller & Strassmann, 2022b ). The source of this fitness cost for hosts is unknown, though there is some evidence that Paraburkholderia itself harms hosts.…”
Section: Introductionmentioning
confidence: 99%
“…The source of this fitness cost for hosts is unknown, though there is some evidence that Paraburkholderia itself harms hosts. For example, the density of Paraburkholderia tends to be associated with lower host spore production ( Scott, Queller & Strassmann, 2022a , 2022b ; Noh et al, 2024 ) and Paraburkholderia infection interferes with host immune cells that develop during the multicellular stage ( Scott et al, 2023a ).…”
Section: Introductionmentioning
confidence: 99%
“…Among this latter category are Paraburkholderia agricolaris, P. hayleyella and P. bonniea, which persistently infect D. discoideum cells as intracellular passengers [ 29 ]. Though in many respects Paraburkholderia acts as a pathogen, reducing the apparent fitness of its host, infection by Paraburkholderia imbues D. discoideum with the ability to carry prey bacteria with it throughout the social stages of its life cycle [ 30 32 ]. This bacterial carriage can enable D. discoideum to disperse to prey-impoverished environments not available to uninfected D. discoideum.…”
Section: Introductionmentioning
confidence: 99%